Multiple in situ Nucleic Acid Collections (MISNAC) From Deep-Sea Waters - Wei, Zhan-Fei; Li, Wen-Li; Li, Jun; Chen, Jun; Xin, Yong-Zhi; He, Li-Sheng; Wang, Yong (Frontiers in Marine Science, 2020)
To obtain an accurate picture of microbial processes is essential for in-depth understanding of the dynamics of microbial communities and metabolic potentials. In this study, an apparatus for automatic multiple in situ nucleic acid collections (MISNAC) loaded and controlled by a lander was designed and applied for in situ microbial filtration, cell lysis and nucleic acid collection at different time points during three cruises in the South China Sea. The MISNAC apparatus completed 390 L in situ water filtration and collected a total of 1,176 ng DNA with six working units in four deployments at ∼1,000 m depth. Microbial community structures in water samples obtained by the MISNAC and in situ microbial filtration and fixation (ISMIFF) apparatus, respectively, were compared by analyzing sequences of 16S rRNA amplicons. The result showed that these communities were largely consistent, regardless of the differences in the communities in the samples from different cruises and time points. In addition, the transcriptomes of the samples collected by the MISANC and a Niskin bottle dramatically differed in abundance and diversity of 16S rRNA gene reads, indicating that more in situ RNA molecules were preserved by the MISNAC, compared to the Niskin. The application of the MISNAC apparatus paved the way to time-series changes of deep-sea microorganisms and their response to various environmental factors.